Interaksi Manusia sebagai Makhluk Sosial dalam Ruang Publik menurut Jürgen Habermas: Studi Kasus Pameran Metamorfosart 6 - Ifna Dini Rizkiyah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This article will examine a concept of public space from Jurgen Habermas' perspective with a focus on the dynamics of human social interaction as social creatures in the broad public space zone. Through a detailed analysis of Jurgen Habermas' thoughts, this article will answer how a public space has a function as an arena where individuals and groups will participate in public discourse, such as forming recreational activities, forming academic activity venues, building social and cultural activities. , initiating a mindset in the form of opinions, ideas, ideas, discussions, and together building a context. Apart from all that, this article will also describe the challenges faced by contemporary public space zones in the digital and globalization era, focusing on the application of Jürgen Habermas' public space concept which offers a rich analytical framework for understanding the dynamics of social interaction in the context of modern society. Thus, it is hoped that writing this article will be able to contribute to the development of theory, reasoning and practice that is relevant to contemporary issues surrounding public space, such as the situation of public space as conceived from Jurgen Habermas' perspective.